Crystal structure of 2,4-dinitrophenyl 2,4,6-trimethylbenzenesulfonate - Stenfors, Brock Anton; Ngassa, Felix Nyuangem (European Journal of Chemistry, 2022)
Arylsulfonates are a useful class of synthetic precursors, affording either their arylamine or arylsulfonamide counterparts upon amination via regioselective C–O/S–O bond cleavage. Herein, the synthesis of 2,4-dinitrophenyl 2,4,6-trimethylbenzenesulfonate is described, utilizing our previously developed synthetic methods, and crystallographic characterization. While the mechanism for nucleophilic substitution at the sulfonyl group remains largely unknown, experimental work within our group and in the literature lend credence to a mechanism analogous to its carbonyl counterpart. Characterization of the molecular structure of the title compound, C15H14N2O7S, at 173 K, features a sulfonate group with S=O bond lengths of 1.4198(19) and 1.4183(19) Å and a S–O bond length of 1.6387(18) Å. Viewing down the S–O bond reveals gauche oriented aromatic rings. Crystal data for C15H14N2O7S: Monoclinic, space group P21/c (no. 14), a = 6.8773(10) Å, b = 8.9070(14) Å, c = 25.557(4) Å, β = 93.0630(18)°, V = 1563.3(4) Å3, Z = 4, T = 173.15 K, μ(MoKα) = 0.251 mm-1, Dcalc = 1.557 g/cm3, 12259 reflections measured (3.192° ≤ 2Θ ≤ 50.682°), 2861 unique (Rint = 0.0493, Rsigma = 0.0419) which were used in all calculations. The final R1 was 0.0457 (I > 2σ(I)) and wR2 was 0.1306 (all data).